Knowledges, beliefs and practices on radiation protection of non-radiologists physicians who use ionizing radiation and participate in radioscopically guided procedures - Kapsampelis, Markos; Intas, George; Lavdas, Eleftherios; Stergiannis, Pantelis; Bakas, Athanasios (Health & Research Journal, 2025)
Background: Technical innovations have spread the use of ionizing radiation in daily clinical practice. About one third to half medical decisions are guided by radiological examinations. This review aims to evaluate current literature relating non-radiologists physicians' knowledge and practices of radiation safety. Method and Material: A literature search from the MEDLINE and CINAHL databases was performed where original articles were retrieved, published in the English language from the past 10 years. Results: While almost all physicians use lead aprons not all of them use thyroid protectors and very few of them use lead gowns and goggles. Also the majority of physicians do not use a dosimeter badge. The major reason for not using radiation protection equipment is their unavailability. Physicians have low levels of knowledge about radiological safety. Longer length of service, having attended a radiation protection and safety course, increased frequency of ordering imaging per day and specialty are factors that affect positively physicians’ level of knowledge. Although occupational radiation exposure has been associated with leukemia and nonmalignant thyroid nodular disease, increased risk of cancer, cataract, headache and fatigue, eye symptoms with most common the red eyes, very few physicians have read articles on radiation safety or have received training. Conclusions: The inadequate level of radiation knowledge can lead to increased radiation exposure and risk for complications to healthcare professionals and patients. Healthcare organizations must ensure the adequate procurement of personal protective equipment so it is available to physicians who use ionizing radiation.